PENDAMPINGAN AKAD DALAM PENYUSUNAN PRODUK SYARIAH PADA PENDIRIAN KOPERASI IIQ JAKARTATINJAUAN NORMATIF ATAS DESAIN PRODUK, DOKUMEN AKAD, DAN TATA KELOLA KELEMBAGAAN - Sultan Antus Nasruddin (LPPM STAI Muhammadiyah Probolinggo, 2025)
This article discusses the importance of sharia contract mentoring (pendampingan akad) in developing sharia products during the establishment phase of the IIQ Jakarta Cooperative. The primary focus is to ensure that the institutional design, types of services, contract documents, and operational procedures of the cooperative align with sharia principles and prevailing positive law. The method utilized is a normative-juridical approach, examining laws and regulations, the fatwas of the National Sharia Board of the Indonesian Council of Ulama (DSN-MUI), and relevant academic works concerning the practices of sharia cooperative products. The results indicate that sharia contract mentoring should not be understood merely as selecting Arabic terminology for a product, but rather as a process of aligning members' needs, transaction characteristics, risk-sharing, profit mechanisms, agreement documents, and sharia supervision. During the establishment phase, the products that are generally relevant to be developed include mudharabah-based deposits, syirkah or mudharabah-based business financing, murabahah-based goods financing, ijarah-based service financing, and qardh-based benevolent funds. This article asserts that contract mentoring from the initial establishment phase will minimize the risk of product deviations, clarify the rights and obligations of the parties involved, strengthen members' trust, and provide a sound foundation for the growth of campus-based sharia cooperatives.